Back to the Future of qEEG: Lifespan Normative Modeling of Spectral Ratios and Functional Indices with Potential Applications to Therapeutic Monitoring - J. Bosch-Bayard; J. Guerrero-Sauzameda; R. I. Bosch-Bayard; R. Pérez-Elvira; A. Bosch-Castro; J. Sánchez-Rodríguez; A. Flores; K. Flores; E Resendiz-Flores; A. Ferrando; P. Ferrando; L. Galán-García; et al. (Brain Topography, 2026)
Quantitative EEG (qEEG) provides objective, millisecond-resolution measures of brain dynamics. Despite decades of methodological advances, clinically relevant derived indices—spectral power ratios, cognitive-emotional state markers, and physiological parameters—are typically reported as raw values without the normative context required for individualized clinical inference. To develop the first systematic age-dependent normative models for this family of derived qEEG indices using a multinational database, enabling probabilistic Z-score interpretation at the individual level with potential applications in objective therapeutic monitoring. Normative modeling was applied to the HarMNqEEG database ( n = 1,564 neurologically healthy participants, ages 5–97, 9 countries, eyes-closed resting state). Electrode-level Spectral Normalization (ESN) removed inter-individual and inter-device amplitude variability while preserving the neurophysiological interpretability of each index. Age-dependent normative trajectories were estimated using Generalized Additive Models for Location, Scale, and Shape (GAMLSS) with P-splines on log(age), allowing conditional mean and variance to vary non-linearly across the lifespan. GAMLSS modeling revealed significant non-linear age-dependent trajectories for all indices. Slow-wave-dominated ratios showed steep decreases from childhood to early adulthood, consistent with cortical maturation; alpha-dominated indices increased during adolescence before stabilizing. ESN normalization yielded well-calibrated normative residuals across the full age range for all indices, except Valence. For the Valence index, a quantile regression model is provided as the recommended normative reference due to its spike-and-slab marginal distribution. These normative models provide a principled, age-adjusted probabilistic framework for individual-level qEEG interpretation, based on eyes closed resting state recordings, laying the methodological groundwork for future clinical validation in diagnostic and therapeutic monitoring applications. The ESN strategy requires no knowledge of recording equipment, ensuring broad applicability across clinical and research settings.

Optimization of protein requirements and feed restriction in Penaeus vannamei (Boone, 1931) biofloc culture - S. Ferrando-Juan; J. Gómez-Aguilera; S. Martínez-Llorens; A. Tomás-Vidal; M. Rodilla; M. Jover-Cerdá; F. J. Moyano; D. S. Peñaranda (Aquaculture International, 2026)

Seed banking of mediterranean coastal plants: an analysis to identify current seed availability and gaps to guide future seed collection and habitat restoration activities - Marcello De Vitis; Valter Di Cecco; Mohamed Abdelaal; Gianluigi Bacchetta; Jože Bavcon; Kenza Saadiya Benmenni; Maurizio Bianchelli; Magda Bou Dagher Kharrat; Joseph A. Buhagiar; Francesca Carruggio; Angelino Carta; Simona Casavecchia; et al. (Journal of Coastal Conservation, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Will the EU deforestation-free products regulation (EUDR) reduce tropical forest loss? Insights from three producer countries - Roldan Muradian; Raras Cahyafitri; Tomaso Ferrando; Carolina Grottera; Luiz Jardim-Wanderley; Torsten Krause; Nanang I. Kurniawan; Lasse Loft; Tadzkia Nurshafira; Debie Prabawati-Suwito; Diaz Prasongko; Paula A. Sanchez-Garcia; et al. (Ecological Economics, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Permian thermally-induced shear of the Cossato-Mergozzo-Brissago shear zone in the W-Southalpine basement, Italy: new petrological, geochemical and U–Pb geochronological constraints from the amphibolite-facies units of the Strona Ceneri Border Zone - F. Arboit; A. Decarlis; S. Ferrando; A. Maffeis; S. De Bernardi; A. Ceriani (International Journal of Earth Sciences, 2024)

Update on the status of the contamination by organotin compounds in sediment of Nuevo Gulf, Argentina. Insights from field and experimental studies - N.A. Gomez; J. Sturla Lompré; A. Ferrando; M. Garrido; C.E. Domini (Marine Pollution Bulletin, 2024)

Deep segregation and crystallization of ultra-depleted melts in the sub-ridge mantle - C. Ferrando; G. Borghini; C. Sani; F. Genske; M. Ligi; A. Stracke; A. Sanfilippo (Chemical Geology, 2024)

Phytoplanktonic community and bio-optical properties in coastal waters of an Argentinian Patagonian gulf - L.L. Gracia Villalobos; G.N. Williams; N.G. Glembocki; J.P. Pisoni; A.C. Nocera; A. Ferrando (Marine Pollution Bulletin, 2023)

Differential response of denitrifying and diazotrophic soil populations to short and long-term exposure of glyphosate and atrazine - L. Ferrando; M. I. Bellini; A. Fernández-Scavino (Environmental Sustainability, 2023)

Abundance and diversity of endophytic and rhizospheric diazotrophs associated with rice roots from different rice rotation systems under field conditions - Cecilia Ghiazza; José A. Terra; Lucia Ferrando (Environmental Sustainability, 2023)

Extremophiles as Plant Probiotics to Promote Germination and Alleviate Salt Stress in Soybean - Ana P. Santos; Carolina Belfiore; Cristina Úrbez; Alejandro Ferrando; Miguel A. Blázquez; María E. Farías (Journal of Plant Growth Regulation, 2023)

Molecular markers of DNA repair and brain metabolism correlate with cognition in centenarians - Ines Sanchez-Roman; Beatriz Ferrando; Camilla Myrup Holst; Jonas Mengel-From; Signe Høi Rasmussen; Mikael Thinggaard; Vilhelm A. Bohr; Kaare Christensen; Tinna Stevnsner (GeroScience, 2022)

Metabolic effects of high-intensity interval training and essential amino acids - Katie R. Hirsch; Casey E. Greenwalt; Hannah E. Cabre; Lacey M. Gould; Gabrielle J. Brewer; Malia N. M. Blue; Arny A. Ferrando; Kim M. Huffman; Elizabeth J. Mayer-Davis; Eric D. Ryan; Abbie E. Smith-Ryan (European Journal of Applied Physiology, 2021)

Correction to: Characterization of novel pollen-expressed transcripts reveals their potential roles in pollen heat stress response in Arabidopsis thaliana - Nicholas Rutley; Laetitia Poidevin; Tirza Doniger; Richard L. Tillett; Abhishek Rath; Javier Forment; Gilad Luria; Karen A. Schlauch; Alejandro Ferrando; Jeffery F. Harper; Gad Miller (Plant Reproduction, 2021)

Characterization of novel pollen-expressed transcripts reveals their potential roles in pollen heat stress response in Arabidopsis thaliana - Nicholas Rutley; Laetitia Poidevin; Tirza Doniger; Richard L. Tillett; Abhishek Rath; Javier Forment; Gilad Luria; Karen A. Schlauch; Alejandro Ferrando; Jeffery F. Harper; Gad Miller (Plant Reproduction, 2021)
Key message Arabidopsis pollen transcriptome analysis revealed new intergenic transcripts of unknown function, many of which are long non-coding RNAs, that may function in pollen-specific processes, including the heat stress response. Abstract The male gametophyte is the most heat sensitive of all plant tissues. In recent years, long noncoding RNAs (lncRNAs) have emerged as important components of cellular regulatory networks involved in most biological processes, including response to stress. While examining RNAseq datasets of developing and germinating Arabidopsis thaliana pollen exposed to heat stress (HS), we identified 66 novel and 246 recently annotated intergenic expressed loci (XLOCs) of unknown function, with the majority encoding lncRNAs. Comparison with HS in cauline leaves and other RNAseq experiments indicated that 74% of the 312 XLOCs are pollen-specific, and at least 42% are HS-responsive. Phylogenetic analysis revealed that 96% of the genes evolved recently in Brassicaceae . We found that 50 genes are putative targets of microRNAs and that 30% of the XLOCs contain small open reading frames (ORFs) with homology to protein sequences. Finally, RNAseq of ribosome-protected RNA fragments together with predictions of periodic footprint of the ribosome P-sites indicated that 23 of these ORFs are likely to be translated. Our findings indicate that many of the 312 unknown genes might be functional and play a significant role in pollen biology, including the HS response.

Origin of pyroxenites in the oceanic mantle and their implications on the reactive percolation of depleted melts - V. Basch; Elisabetta Rampone; G. Borghini; C. Ferrando; A. Zanetti (Contributions to Mineralogy and Petrology, 2019)

Determination of probabilities for the generation of high-discharge flows in the middle basin of Elqui River, Chile - Iván P. Vergara Dal Pont; Fernanda A. Santibañez Ossa; Diego Araneo; Francisco J. Ferrando Acuña; Stella M. Moreiras (Natural Hazards, 2018)

Vacchi's palatal organ: a widespread trait in Holocephali - B. Finucci; L. Gallus; A. Amaroli; S. Candiani; M. Rottigni; M. A. Masini; S. Ferrando (Journal of Fish Biology, 2018)
A palatal organ, possibly used for food sorting and processing, has previously been identified among the vomerine toothplates of the chimaeroid Chimaera monstrosa . In this study, the palatal organ was described in six additional species, confirming it is a widespread trait among holocephalans. It is proposed that this palatal structure, which appears to differ in shape according to each chimaeroid's degree of durophagy and is not homologous to the palatal structure described in teleosts, be hereby referred to as Vacchi's organ.

Fragments of the Western Alpine Chain as Historic Ornamental Stones in Turin (Italy): Enhancement of Urban Geological Heritage through Geotourism - A. Borghi; A. d’Atri; L. Martire; D. Castelli; E. Costa; G. Dino; S. E. Favero Longo; S. Ferrando; L. M. Gallo; M. Giardino; C. Groppo; R. Piervittori; et al. (Geoheritage, 2014)

The training-induced changes on automatism, conduction and myocardial refractoriness are not mediated by parasympathetic postganglionic neurons activity - M. Zarzoso; L. Such-Miquel; G. Parra; L. Brines-Ferrando; L. Such; F. J. Chorro; J. Guerrero; A. Guill; J. E. O’Connor; A. Alberola (European Journal of Applied Physiology, 2012)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Polymorphism of the Goat Agouti Signaling Protein Gene and Its Relationship with Coat Color in Italian and Spanish Breeds - B. Badaoui; M. D’Andrea; F. Pilla; J. Capote; A. Zidi; J. Jordana; A. Ferrando; J. V. Delgado; A. Martínez; O. Vidal; M. Amills (Biochemical Genetics, 2011)

Genetic diversity and landscape genetic structure of otter (Lutra lutra) populations in Europe - Nadia Mucci; Johanna Arrendal; Hermann Ansorge; Michael Bailey; Michaela Bodner; Miguel Delibes; Ainhoa Ferrando; Pascal Fournier; Christine Fournier; José A. Godoy; Petra Hajkova; Silke Hauer; et al. (Conservation Genetics, 2010)

Light, sediment, temperature, and the early life-history of the habitat-forming alga Cystoseira barbata - Andrew D. Irving; David Balata; Francesco Colosio; Guillaume A. Ferrando; Laura Airoldi (Marine Biology, 2009)

Population genetic structure and distribution of introduced American mink (Mustela vison) in Spain, based on microsatellite variation - Roberta Lecis; A. Ferrando; J. Ruiz-Olmo; S. Mañas; X. Domingo-Roura (Conservation Genetics, 2008)

Composition and thermal structure of the lithosphere beneath the Ethiopian plateau: evidence from mantle xenoliths in basanites, Injibara, Lake Tana Province - S. Ferrando; M. L. Frezzotti; E.-R. Neumann; G. De Astis; A. Peccerillo; A. Dereje; Y. Gezahegn; A. Teklewold (Mineralogy and Petrology, 2008)

Sublethal Bioconcentration of Fenitrothion in the Blood and Brain of the European Eel - E. Sancho; M. D. Ferrando; A. Ten; C. Lleó; E. Andreu-Moliner (Bulletin of Environmental Contamination and Toxicology, 1998)

Microwave digestion preparation and ICP determination of boron in human plasma - Arny A. Ferrando; Nancy R. Green; Karen W. Barnes; Betsy Woodward (Biological Trace Element Research, 1993)